An Aqueous Electrolyte Gated Artificial Synapse with Synaptic Plasticity Selectively Mediated by Biomolecules - Xu, Xinzhao; Zhang, Haoqin; Shao, Lin; Ma, Rong; Guo, Meng; Liu, Yunqi; Zhao, Yan (Angewandte Chemie, 2023)
The emulation of functions and behaviors of biological synapses using electronic devices has inspired the development of artificial neural networks (ANNs) in biomedical interfaces. Despite the achievements, artificial synapses that can be selectively responsive to non‐electroactive biomolecules and directly operate in biological environments are still lacking. Herein, we report an artificial synapse based on organic electrochemical transistors and investigate the selective modulation of its synaptic plasticity by glucose. The enzymatic reaction between glucose and glucose oxidase results in long‐term modulation of the channel conductance, mimicking selective binding of biomolecules to their receptors and consequent long‐term modulation of the synaptic weight. Moreover, the device shows enhanced synaptic behaviors in the blood serum at a higher glucose concentration, which suggests its potential application in vivo as artificial neurons. This work provides a step towards the fabrication of ANNs with synaptic plasticity selectively mediated by biomolecules for neuro‐prosthetics and human‐machine interfaces. We report an artificial synapse where non‐relevant biomolecules (urea, lactic acid (LA) and fructose (Fru)) cannot modulate its plasticity, while only relevant biomolecules (glucose) can selectively activate the device and induce long‐term modulation and memory effect. The device works properly in blood serum and shows enhanced synaptic behaviors at high glucose concentrations, suggesting its potential application as artificial neurons in vivo.